2019
DOI: 10.1177/0958928719855298
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the image deficit of vocational education and training: Occupational prestige ranking depending on the educational requirements and the skill content of occupations

Abstract: Vocational education and training (VET) often suffers from a lack of social standing among students and their families. Parents have been shown to discard vocational education because of social status maintenance considerations. How adults perceive the social prestige of occupations might therefore be key in understanding the reasons of the image deficit of VET. While the existing literature on occupational prestige ranking stresses the role of the salience in science or the training intensiveness of occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…As the main purpose of higher vocational colleges is to cultivate skilled workers for industries, the difficulty of their entrepreneurial projects is generally low. Moreover, since the students receiving HVE have disadvantages in social capital (Abrassart & Wolter, 2020), their main motivation for starting a business is to secure their livelihood. Therefore, it is unlikely that male and female students would have fundamental differences in their attitudes toward entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main purpose of higher vocational colleges is to cultivate skilled workers for industries, the difficulty of their entrepreneurial projects is generally low. Moreover, since the students receiving HVE have disadvantages in social capital (Abrassart & Wolter, 2020), their main motivation for starting a business is to secure their livelihood. Therefore, it is unlikely that male and female students would have fundamental differences in their attitudes toward entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…While empirical research has suggested that self-efficacy is the strongest individual factor, school entrepreneurship education, and government institutional forces are the main external factors that affect students’ entrepreneurial intention (Nabi et al, 2017; Saeed et al, 2015). Students in the vocational education system often have some disadvantages in social capital, family background and study habits (Abrassart & Wolter, 2020). They defined their career direction in high school, participated in entrepreneurship education to a certain extent, and developed a relationship with the job market earlier than students in the academically oriented general education system.…”
Section: Introductionmentioning
confidence: 99%
“…RRR education (schools, TVET, higher education) can offer young people the opportunity to develop skills useful to their future lives (Houghton, 2019), however, school curricula in RRR areas are often detached from local contexts (Avery, 2013) and time. Although RRR students may understand STEM concepts that they have learnt outside school within their community, such learning may not necessarily align with the established school STEM curricula, particularly if there is a perceived divide between, for example, vocational and academic education (Abrassart and Wolter, 2019) and western and Aboriginal epistemologies (Nakata, 2010). The ways in which community members understand, talk about, model and practice STEM within RRR contexts have been acquired over a considerable time, beginning in early childhood, socialized within the family and continually restructured through encounters with the broader community (Deslandes et al, 2019).…”
Section: Ways Of Knowing Being and Valuing Of Stem Knowledges And Practicesmentioning
confidence: 99%
“…Our data do not enable enquiry into this explanation. Its relevance may be considerable, however, as there are indications that many, especially in privileged social strata, assign little esteem to, but rather look down upon, the low educated (see, for example, Abrassart & Wolter, 2020;Sandel, 2020;Skarpenes & Sakslind, 2020).…”
Section: Discreditmentioning
confidence: 99%